The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1111/j.1472-765x.2007.02213.x
|View full text |Cite
|
Sign up to set email alerts
|

The use of ultrasonic imaging to evaluate the effect of protozoan grazing and movement on the topography of bacterial biofilms

Abstract: Aims:  This study evaluated the effect of protozoan movement and grazing on the topography of a dual‐bacterial biofilm using both conventional light microscopy and a new ultrasonic technique. Methods and Results:  Coupons of dialysis membrane were incubated in Chalkley’s medium for 3 days at 23°C in the presence of bacteria (Pseudomonas aeruginosa and Klebsiella aerogenes) alone, or in co‐culture with the flagellate Bodo designis, the ciliate Tetrahymena pyriformis or the amoeba Acanthamoeba castellanii. Amoeb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 36 publications
(89 reference statements)
2
14
0
Order By: Relevance
“…The susceptibility of P. costantinii and S. plymuthica biofilms to Tetrahymena sp. grazing is consistent with prior studies in which filterfeeding ciliates have been found to graze efficiently upon biofilms and induce significant changes in biofilm morphology (25,47,71).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The susceptibility of P. costantinii and S. plymuthica biofilms to Tetrahymena sp. grazing is consistent with prior studies in which filterfeeding ciliates have been found to graze efficiently upon biofilms and induce significant changes in biofilm morphology (25,47,71).…”
Section: Discussionsupporting
confidence: 80%
“…may be relatively less successful at feeding upon biofilm cells than suspension feeders. However, comparable ingestion rates have been reported for other surface-dwelling protozoa such as amoebae and Tetrahymena feeding on attached bacteria in mixed-species biofilm (47).…”
Section: Discussionmentioning
confidence: 93%
“…Protozoans in biofilms can have strong impacts on bacterial abundances and spatial heterogeneity, bacterial and microalgal species assemblages, biofilm architecture, and sloughing dynamics (Jackson & Jones 1991, McCormick 1991, Arndt et al 2003, Parry 2004, Parry et al 2007). The diverse protozoans in biofilms have complex trophic interactions, seasonal variations, successional dynamics, and constraints from the flow regime and other environmental factors (Franco et al 1998, Sekar et al 2002, Arndt et al 2003, Gong et al 2005, Wey et al 2008, Norf et al 2009, Risse-Buhl & Küsel 2009.…”
Section: Introductionmentioning
confidence: 99%
“…Laboratory studies have demonstrated that certain specialized grazers are able to efficiently utilize mature bacterial biofilms (Huws et al 2005, Weitere et al 2005). Whether or not surfaceattached microcolonies are resistant to grazing, and if their formation is stimulated by the presence of grazers, might thus be dependent on the dominant grazer types present in the biofilms (Parry et al 2007). Experiments with natural, complex grazer communities are needed to test the role of protozoan grazers in controlling bacterial biofilms in the field.…”
Section: Introductionmentioning
confidence: 99%